(untitled) (Revista Argentina de Musicología, 2018)
This article addresses the different circumstances, needs, approaches and strategies present in the great stories of both popular music and art music in Chile in the twentieth century. It considers the impact produced by the irruption of micro-stories at the beginning of the twenty-first century, focused on the construction of memory of the recent musical past. This, product of a type of independent musical investigation linked to the own protagonists and followers of the musical phenomena addressed. Likewise, the article offers a critical review of the great stories of twentieth-century Chilean art music, observing the repertoire canonization processes and crossings between memory and history. Finally, the text proposes strategies to continue with the historical study of Chilean popular music after the irruption of micro-stories, emphasizing artistic, productive and critical reception aspects that would constitute a “located popular music”, the historical subject on which musicology should prioritize their work.